Effects of nozzle inner surface roughness on the performance of self-resonating cavitating waterjets under different ambient pressures - Li, Deng (Strojniški vestnik, 2017)
The self-resonating cavitating waterjet (SRCW) has been widely used for many practical and industrial applications since the first recognition of its strong cavitation ability. To further improve the performance of SRCW under ambient pressures, the effects of nozzle inner surface roughness were experimentally studied by impinging the jets on pure aluminium specimens (1070A) at various standoff distances. The typical macroscopic appearances and mass losses of the eroded specimens were used to evaluate the performances of the jets issuing from six organ-pipe nozzles of different inner surface roughness values (0.8 %m, 1.6 %m, 3.2 %m, 6.3 %m, 12.5 %m, and 25 %m). The results show that nozzle inner surface roughness significantly influences the optimum standoff distance and the cavitation intensity, which greatly depends on the ambient pressure. Moreover, it is found that there is always an optimum surface roughness that can remarkably enhance the cavitation erosion capability under each ambient pressure. Specifically, at ambient pressures of 2 MPa and 4 MPa, the surface roughness of 6.3 %m causes the strongest cavitation intensity at standoff distances of 42 mm and 50 mm, respectively. While at ambient pressures of 6 MPa, 8 MPa , and 10 MPa, the surface roughness of 12.5 %m is the one that maximally enhances the intensity at standoff distances of 45 mm, 40 mm, and 35 mm, respectively. Furthermore, the enhanced cavitation intensity is found to improve the impingement power of the high-speed waterjet as well. The present study also helps to provide a guideline for determining the finishing accuracy of inner surface required in the fabrication of organ-pipe nozzles.
Keywords: debelina viskoznega podsloja; izguba mase; kavitacijska erozija; orgelska šoba; površinska hrapavost; samoresonančni kavitacijski vodni curek; tlak okolice